The Added Value of Oscars and Festival Awards - Mazierska, Ewa Hanna (Załącznik Kulturoznawczy, 2021)
This article discusses the value of the Academy Awards and awards received by filmmakers at film festivals, as well as other advantages of participating in them. It does so by taking into consideration several aspects of film awards: their effect on the monetary profit made by the winning films, their effect on the construction of the film canon and the ‘cinematic map’ of the world. It also examines factors conducive to receiving awards, such as successful marketing campaigns and tackling certain topics, as well as considers the argument that film awards have lost some of their value in recent years. The article is based on secondary research about Oscars and film festivals, a large part of which is based on journalistic sources, reflecting the fact that much of the data is new and hence has not yet been properly digested by the academic community.